Reskilling and Upskilling Strategies for Manufacturing Workers in the Industry 4.0 Landscape: Case study on PT. XYZ - Fatur Rizki, Dwiki; Mangesti, Dewi Sri; Alfin, Muhammad; Ratnasari, Pungky Eka; Purnamasari, Rita (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The advent of Industry 4.0 has revolutionized the manufacturing sector, necessitating a paradigm shift in workforce skills to adapt to the rapid technological advancements. This paper explores the strategies for reskilling and upskilling manufacturing workers at PT. XYZ to align with the demands of Industry 4.0. The research utilizes a mixed-method approach, combining quantitative data from employee performance metrics and qualitative insights from interviews with management and workers. Key findings indicate that a comprehensive strategy integrating technical training, digital literacy, and soft skills development is essential for enhancing employee adaptability and performance. The case study highlights the pivotal role of organizational culture and leadership in driving successful reskilling and upskilling initiatives. Furthermore, the research underscores the importance of continuous learning and proactive workforce planning to mitigate skill gaps and ensure sustainable growth. The implications of this study provide valuable insights for manufacturing firms aiming to thrive in the Industry 4.0 landscape through strategic human capital development